Preparation and Characterization of Sustained Release Anti-Diabetic Tablet by Using Natural Polymer - Mishra, Amul N; Yadav, Chandni (Journal of Neonatal Surgery, 2025)
Hyperglycaemia is the result of diabetes mellitus, which is a metabolic condition that is characterized by an inadequate generation of endogenous insulin, with or without resistance to the action of insulin. Type 1 diabetes mellitus is characterized by a failure in insulin production due to the destruction of the β cells of the pancreas. Patients with this condition require insulin treatment. On the other hand, type 2 diabetes can be characterized by defects in both insulin action (also known as insulin resistance) and insulin secretion, and it is associated with elevated basal hepatic glucose production due to the presence of insulin resistance. Gliclazide is a sulfonylurea of the second generation that is commonly recommended to treat type II diabetes. It has the ability to decrease the level of glucose in the blood of humans in an immediate manner by increasing the release of insulin from the pancreas inside the body. Altering the concentration of the guargum/ xanthan gum and carrageenan that was employed as a polymer allowed for the preparation of a variety of different formulations. From the perspective of the release pattern, the promising formulation was evaluated in comparison to the commercially available sample of sustained-release product. It was shown that increasing the concentration of the matrix tablet as well as the viscosity of the polymer resulted in a reduction in the release rate of gliclazide. It is possible that this is the result of greater swelling and a decreased rate of erosion experienced by the matrix tablet.